2003
DOI: 10.1023/a:1024084108803
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sulfonamides and trimethoprim are chemotherapeutics that are extensively used in various animal species. Little information about the pharmacokinetics of these compounds in chickens exists in the literature. In this study, a new commercial formulation of sulfadiazine in combination with trimethoprim was administered both intravenously and orally, according to a crossover design, to healthy, 7-week-old broilers. The plasma concentrations of the drugs were determined by validated high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
1
13
2
1
Order By: Relevance
“…Others researchers reported different half-lives for SDA ranging from 1.13 h from Dagorn et al (1991) to 2.8 h from Batzias et al (2000). In the present study, the half-life values of SDA for all three preparations were higher than those reported previously by Löscher et al (1990) and Baert et al (2003). This extended half-life could be due to delayed absorption caused by the presence of food in the intestine or differences in oral dose administration.…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…Others researchers reported different half-lives for SDA ranging from 1.13 h from Dagorn et al (1991) to 2.8 h from Batzias et al (2000). In the present study, the half-life values of SDA for all three preparations were higher than those reported previously by Löscher et al (1990) and Baert et al (2003). This extended half-life could be due to delayed absorption caused by the presence of food in the intestine or differences in oral dose administration.…”
Section: Discussioncontrasting
confidence: 81%
“…Löscher et al (1990) reported that SDA and TMP were rapidly eliminated from plasma following oral administration, with half-lives of 2.7 h and 1 h, respectively. In contrast Baert et al (2003) reported mean half-lives of 3.2 h and 3.71 h following intravenous or oral administration of SDA (33.34 mg/kg), respectively. Others researchers reported different half-lives for SDA ranging from 1.13 h from Dagorn et al (1991) to 2.8 h from Batzias et al (2000).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations